METHODS OF TREATMENT UNDER THE INFLUENCE OF MUSIC IN MEDICINE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Music therapy is a psychotherapeutic method that uses music as a therapeutic tool. It is aimed at improving the physical and mental health of a person and is based on the healing properties of music. The article also discusses the influence of music and art on human psychology, its role and importance. It also describes the psychological properties and pedagogical possibilities of music.